A Review on the Advanced Maintenance Approach for Achieving the Zero-Defect Manufacturing System - Jun, Hong-Bae (Frontiers in Manufacturing Technology, 2022)
Recently, a revolutionary change is taking place in manufacturing and production systems thanks to the development of various advanced technologies such as IIoT (Industrial Internet of Things), CPPS(Cyber-Physical Production System), digital twins, big data analytics, AI (Artificial Intelligence), and so on. One of the change is that} manufacturing and production systems are now trying to transform into the ZDM (Zero-Defect Manufacturing) system. \textcolor{red}{For a manufacturing company, quality takes precedence over any other competitive factors, so the implementation of a ZDM system is very important. For the implementation of ZDM,} many fundamental technologies are required. Among them, the advanced maintenance approach for the facilities/equipment of the manufacturing and production system is much more important because it could support the zero-defect and high-efficiency operation of manufacturing and production systems. The advanced maintenance approach, which is often called by various terms such as predictive maintenance, condition-based maintenance plus (CBM+), and PHM (Prognostics and Health Management), requires various interdisciplinary knowledge and systematic integration. In this study, we will review previous works \textcolor{red}{mainly focusing on advanced maintenance subject among ZDM research works}, and briefly discuss the challenging issues for applying PHM technologies to the ZDM.